Production of free bile acids by bacterial deconjugation from conjugated bile acids derived from peptone in a medium - MOROTOMI, Masami; MAKINO, Takashi; SATOU, Mikiko; SAKAITANI, Yukiko; TAKAHASHI, Takuya (Nihon saikingaku zasshi, 1996)
In the course of studies of in vitro bile acid transformation by lactic acid bacteria, we noticed that the medium used contained conjugated bile acids. HPLC analysis of the medium for each component indicated that these bile acids had originated from a peptone (Bacto Peptone, Difco). The concentration of these bile acids in a medium containing 2% Bacto Peptone was greater than 200μM, higher than the concentration of bile acids usually added in in vitro bile acid transformation studies. Therefore, in such studies, it would be necessary to distinguish between the production of free secondary bile acids by bacterial deconjugation and that by 7α-dehydroxylation. Since bile acids affect not only bacterial growth but also many metabolic activities, particular attention should be given to the use of Bacto Peptone in the medium.